ANALISIS PERANAN PAJAK DAERAH DALAM RANGKA PENINGKATAN PENDAPATAN DAERAH KOTA PROBOLINGGO - Nugroho, Yanuar Fajar (Jurnal Mahasiswa Perpajakan, 2015)
This research is aims are to understand and explain the efforts that made by Probolinggoâ€™s Government. The researcher is discussed about obstacles, contribution tax local, also role ofÂ  tax local in term of the increasing increasing of local tax. The methods used in this research is descriptive qualitative. This research is expected to deliver benefits and a good influence for improving revenue area Of Probolinggo. Keyowords: Role, Local Tax, Revenue